(untitled) (Journal Of Educational and Psychological Researches, 2015)
The current research aimed to identify: • Social perception among university students. • Differences in social Perception according to the variables: Gander` (male, female) b- theme (scientific, humanitarian( • Moral judgments among university students. • Differences in moral judgments according to two variables: A-type (male, female) b- theme (scientific, humanitarian) • Emotional tranquility among university students. • Differences in emotional tranquility according to two variables: A-type (male, female) b- theme (scientific, humanitarian) • Contributionof socialperception and moral judgments inemotional Tranquility. To achieve the objectives of the research, the researcher building social perceptionScale and tranquility emotional and adoption of measure of Kohlberg, after extracting the validity and reliability and strength discriminatory in Vaqrathm, applied on a sample of 400 students from Baghdad University students have been selected in the manner stratified random, and after the data analysis and processing Find out statistically significant set of findings and recommendations and proposals